Optimization algorithms for networks and graphs - Evans, James R. (James Robert) 1950- (M. Dekker, 1992)
A revised and expanded advanced-undergraduate/graduate text (first ed., 1978) about optimization algorithms for problems that can be formulated on graphs and networks.